Basic competency of pancasila ideological education for elementary school in Indonesia - Yadi Ruyadi; Asep Dahliyana (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aims to map and formulate basic competencies that must be mastered by elementary school students in Pancasila Ideology Education. This study used a mixed-method approach through the Design-Based Research (DBR) technique with 80 elementary school students in Subang Regency through purposive sampling. This study resulted in the basic competencies of Pancasila Ideology Education for lower grade students (grades 1-3 of elementary school) and upper grades (grades 4-6 of elementary school) based on Bloom's theory. The formulation of the basic competencies of Pancasila Ideology Education in elementary schools must consider the level of development of students and be by philosophical, academic, juridical, and sociological basics. The research implies that the government through the Department of Education and Culture must be able to implement the development of Pancasila ideology through the moral development of students as an effort to understand, appreciate, and practice tiered Pancasila values informal educational institutions.